Direct evidence of traps controlling the carriers transport in SnO2 nanobelts - Berengue, Olivia M. [UNESP]; Chiquito, Adenilson J. (IOP Publishing, 2017)
This work reports on direct evidence of localized states in undoped SnO2 nanobelts. Effects of disorder and electron localization were observed in Schottky barrier dependence on the temperature and in thermally stimulated currents. A transition from thermal activation to hopping transport mechanisms was also observed. The energy levels found by thermally stimulated current experiments were in close agreement with transport data confirming the role of localization in determining the properties of devices.
Keywords: SnO2; transport; trap